Sucrose-Induced Proteomic Response and Carbohydrate Utilization of Lactobacillus sakei TMW 1.411 During Dextran Formation - Prechtl, Roman M.; Janßen, Dorothee; Behr, Jürgen; Ludwig, Christina; Küster, Bernhard; Vogel, Rudi F.; Jakob, Frank (Frontiers in Microbiology, 2018)
Lactobacillus (L.) sakei belongs to the dominating lactic acid bacteria in indigenous meat fermentations, while diverse strains of this species have also been isolated from plant fermentations. We could recently show, that L. sakei TMW 1.411 produces dextran from sucrose even at cold and salt stress, indicating its applicability as dextran forming starter culture for the manufacturing of fat-reduced meat products. However, the general physiological response of L. sakei to sucrose as carbohydrate source has not been investigated yet, especially upon simultaneous dextran formation. To address this lack of knowledge, we sequenced the genome of L. sakei TMW 1.411 and performed a label-free, quantitative proteomics approach to investigate the sucrose-induced changes in the proteomic profile of this strain in comparison to its proteomic response to glucose. In total, 21 proteins were found to be differentially expressed at the applied significance criteria (FDR ≤ 0.01). More than 50% of the differentially expressed proteins were associated with the carbohydrate metabolism and were specifically upregulated upon growth on sucrose including several enzymes, which enable sucrose and fructose uptake as well as their subsequent intracellular metabolization, respectively. The plasmid-encoded, extracellular dextransucrase of L. sakei TMW 1.411 was expressed at high levels irrespective of the present carbohydrate and was predominantly responsible for sucrose consumption in growth experiments using sucrose as sole carbohydrate source, while the released fructose from the dextransucrase reaction was more preferably taken up and intracellularly metabolized than sucrose. Genomic comparisons revealed, that operons coding for uptake and intracellular metabolism of sucrose and fructose are chromosomally conserved among L. sakei, while plasmid-located dextransucrase genes are present only in few strains. In accordance with these findings, 59 different L. sakei strains of our strain collection were able to grow on sucrose as sole carbohydrate source, while 8 of them exhibited a mucous phenotype on agar plates indicating dextran formation from sucrose. Our study therefore highlights the intrinsic adaption of L. sakei to plant environments, in which sucrose is abundant, and opens new possibilities regarding the use of L. sakei in novel meat fermentation processes, to which sucrose could be intentionally added as carbon source.